THE RELATIONSHIP BETWEEN KNOWLEDGE AND ATTITUDE OF WOMEN OF REPRODUCTIVE AGE ABOUT LEBER RAHUM CANCER WITH BEHAVIOR OF UTILIZING TONT INSPECTION SERVICE VISUALK ACETIC ACID (IVA) IN PANOMBEAN PUSKESMAS WORKING AREA - Yunardi (MEDALION JOURNAL: Medical Research, Nursing, Health and Midwife Participation, 2022)
Knowledge about cervical cancer in Indonesia is still relatively low, only about 246 of women in Indonesia know about cervical cancer, so researchers are interested in examining the relationship between knowledge and attitudes of women of childbearing age about cervical cancer and the behavior of using Acetic Acid Visual Inspection (IVA) in Indonesia. Work Area of ​​the Panombean Panei Health Center in 2017. This research is descriptive in nature which was carried out in the Work Area of ​​the Panombean Panei Health Center in May-July 2017 with a population of 300 people and a sample of 75 people. The results of this study indicate that the majority of high school respondents were 40 people (53.3″o), a minority of junior high school were 16 people (21,390), the majority were farmers, namely 27 people (3,699), a minority of civil servants, namely 10 people (13,390), the majority of knowledge was lacking, namely as many as 62 people (82.7Y40), the minority of good knowledge is 13 people (17.3”6), the majority disagrees is 55 people (73.396), the minority agrees is 20 people (26.7”0), the majority have never used the Acetic Acid Visual Inspection examination ( IVA), namely 60 people (80Y6), the minority had used the Acetic Acid Visual Inspection (IVA) examination, namely 15 people (2096). From the results of the chisguare test it was concluded that knowledge has a relationship with the behavior of utilizing the Acetic Acid Visual Inspection (IVA) examination in the Work Area of ​​the Panombean Panei Health Center in 2017, because the p value < 0.05.